2008
DOI: 10.3181/0706-rm-155
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Dysfunction and Redox Signaling in Atrial Tachyarrhythmia

Abstract: Accumulating evidence links calcium-overload and oxidative stress to atrial remodeling during atrial fibrillation (AF). Furthermore, atrial remodeling appears to increase atrial thrombogeneity, characterized by increased expression of adhesion molecules. The aim of this study was to assess mitochondrial dysfunction and oxidative stress-activated signal transduction (nuclear factor-kappaB [NF-kappa B], lectin-like oxidized low-density lipoprotein receptor [LOX-1], intercellular adhesion molecule-1 [ICAM-1], and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
98
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 95 publications
(98 citation statements)
references
References 62 publications
0
98
0
Order By: Relevance
“…Results of our group demonstrated the involvement of LOX-1 in the oxidative state within the right atrium in patients with AF. 55 Importantly, increased ''oxidative stress'' contributes to a pro-inflammatory and prothrombotic state of the atrial endomyocardium during AF. Obviously, future experiments should elucidate the in vivo relevance of E2 on atrial protection mechanisms.…”
mentioning
confidence: 99%
“…Results of our group demonstrated the involvement of LOX-1 in the oxidative state within the right atrium in patients with AF. 55 Importantly, increased ''oxidative stress'' contributes to a pro-inflammatory and prothrombotic state of the atrial endomyocardium during AF. Obviously, future experiments should elucidate the in vivo relevance of E2 on atrial protection mechanisms.…”
mentioning
confidence: 99%
“…mRNA and protein levels of the transcrip- tion factor nuclear factor -B (NF-B) were increased in an atrial tachypacing canine model. Two research groups identified an accumulation of NF-B in human atrial tissue slices subjected to rapid pacing for 24 h, as well as in AF patients [37]. We verified that enhancement of NF-B up-regulated miR-328 transcription, using a chromatin immunoprecipitation assay.…”
Section: Modulation Of Mirnas By Transcription Factorsmentioning
confidence: 69%
“…Abraham et al presented an electromechanical dysfunction of myocardial specimens after remote exogenous ischemia-reperfusion [25], Canty et al determined the activation of oxidative stress-responsive transcription factor in homogenized auricule tissue [27]. Atrial tissue was also used by Bukowska et al for in vitro pacing experiments [28]. Wang et al proved the cardioprotective effect of osteopontin against cardiac ischemia-reperfusion injury by measuring the SOD activity and MDA content in cells [29].…”
Section: Discussionmentioning
confidence: 99%